The Influence of Transformational Leadership, Compensation, Organizational Climate, Work Satisfaction on the Performance of Puskesmas Kijang Employees in Bintan Regency - Verlina Y Kawangung; Putri Rahmawati; Faisal Husni; Didi Kurniadi (IAIC International Conference Series, 2021)
This study uses a causal model survey method using path analysis techniques. The aims of this study is to confirm the theoretical model with empirical data, the study population is employees at Kijang Health Center in Bintan Regency, which consists of civil servants and temporary employees with samples of 44 employees. Data collecting technical using variable measurements by questionnaire instruments, this instrument was developed based on theoretical studies. Data analysis uses descriptive statistics and analysis statistics. Statistical tests are used to test the significance of path coefficients using Partial Least Square (PLS), which is a Multivariate Analysis in the second generation using structural equation modeling (SEM). PLS can be used for a small number of samples and does not require the assumption that data distribution must be normal or not. The relationships between variables formulated in the formulation of the problem as many as 6 pieces obtained significant results.